Analysis the Estimates of Inequality Human Development Index to Determine the Efficiency of Human Resources By the Distribution Disparity Between Iraq’s Population With Reference to Kurdistan Region - Aqrawi, ZAki Mati; Muhammad, Rebar Fatah (Journal of University of Human Development, 2016)
quire access to a continuous human development is relying on real development policies, that are based on dealing with the various interconnected aspects of society, through supporting the investment aspects within the potential of individuals and the fight against poverty and to reduce unemployment, as well as the development of health, education and income and achieve relative justice in the distribution among population, leading to the development progress according to gender equality and the empowerment of citizens, various categories of promising to participate in the community, in addition to the decision-processors to cope the demographic and environmental pressures . Human Development indicate through its traditional index to the level of achievement of the areas that have been mentioned in although of this index does not indicate conclusively measure of the true levels of human development in all countries accuracy due to the influence of many factors, including differences in regulations, economic conditions, political privacy, and others, so it was necessary to find alternatives, by developing indicators of (AHDI) and index of inequality and other necessary indicators required to be more realistic, so it was in this research analysis the estimates of inequality human development index detailed for its three dimensions in Iraq for the years 2012, 2013 and 2014 through the introducing of inequality factor in the calculation of these elements, and to assess the inequality human development index based its equation which is: The results showed the inequality index equal to (0.464 0.579 0.505) depending on the its inequality dimensions, which were values (0.622 , 0.334 , 0.481) (0.622 , 0.328 , 0.626) (0.727 , 0.559 , 0.477) for each of the health, education and income, respectively, for the years mentioned, while the value of the original human development or traditional evidence is equal (0.590 , 0.642 , 0.694). This indicates the existence of a difference between the two indexes which were calculated using the formula: ) 105 ( This difference is due to the lack of equality between the original and inequality indexes as a result of the lack of full equality in society, as it achieved equal to the indexes at achieving full equality, but in the case of inequality, i ts index will be less than the original, and this which appeared in this research, that means it compatible with fundamentals theory and previous studies in this area. Were also analyzed the results of the contrast between the two indexes in the Kurdistan Region and analyze comparisons between the values at the level of the region and the center. Based on the findings and conclusions a number of suggestions were putted in order to reach an advanced level of human development in Iraq, the most important achievement of the overall human security and openness to the outside world in the presence of a rational policy-based management supported consciously social correlative and components and qualified manpower institutions advanced levels contribute to the comprehensive development, the performance of human resources and achieve the aspirations of individuals in the community